2023
DOI: 10.1161/atvbaha.122.318160
|View full text |Cite
|
Sign up to set email alerts
|

A New Autosomal Myh11-CreER T2 Smooth Muscle Cell Lineage Tracing and Gene Knockout Mouse Model—Brief Report

Abstract: Background: The Myh11 promoter is extensively used as a smooth muscle cell (SMC) Cre-driver and is regarded as the most restrictive and specific promoter available to study SMCs. Unfortunately, in the existing Myh11-CreER T 2 mouse, the transgene was inserted on the Y chromosome precluding the study of female mice. Given the importance of including sex as a biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…In this issue of Arteriosclerosis, Thrombosis, and Vascular Biology , Deaton et al 17 describe the generation of a novel bacterial artificial chromosome–based Myh11-CreER T2 -RAD mouse line, in which bacterial artificial chromosome insertion occurred on chromosome 2. The authors present a rigorous side-by-side analysis of the old and the new Myh11-CreER T2 mouse lines and provide robust data indicating that the new line is equivalent to the original with the advantage of allowing experiments in male and in female Myh11-CreER T2 mice (Figure 1).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In this issue of Arteriosclerosis, Thrombosis, and Vascular Biology , Deaton et al 17 describe the generation of a novel bacterial artificial chromosome–based Myh11-CreER T2 -RAD mouse line, in which bacterial artificial chromosome insertion occurred on chromosome 2. The authors present a rigorous side-by-side analysis of the old and the new Myh11-CreER T2 mouse lines and provide robust data indicating that the new line is equivalent to the original with the advantage of allowing experiments in male and in female Myh11-CreER T2 mice (Figure 1).…”
mentioning
confidence: 99%
“…This leakiness is SMC-specific and is also seen in the original Myh11-CreER T2 -Off line. 17 It is most likely due to a small fraction of the CreER T 2 protein which escapes the cytoplasmic sequestration mechanisms in the absence of tamoxifen, including binding to heat shock protein 90, and then translocates to the nucleus. Interestingly, Deaton et al 17 demonstrated that the degree of age-dependent tamoxifen-independent recombination varies between different floxed alleles.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4 These facts together with our findings demand further studies to fully characterize the genetic defects and their biological consequences for the Myh11-CreER mouse, so that critical information may be applied when revisiting previous studies involving the use of this mouse. The newly developed autosomal Myh11-CreER 5 and Itga8-CreER 3 mouse lines may serve well for this purpose.…”
mentioning
confidence: 99%